Histological evaluation of the rat dental pulp after indirect capping with sildenafil or L-NAME incorporated into a bioadhesive thermoresponsive system - Rogério Rodrigues Cupertino; Franciele Viana Fabri; Vanessa Cristina Veltrini; Miriam Marubayashi Hidalgo; Marcos Luciano Bruschi; Rúbia Maria Monteiro Weffort de Oliveira (Universidade Estadual de Maringá, 2016)
We evaluated the histological dental pulp state in vivo after indirect pulp capping using sildenafil or LG-nitro-L-arginine (L-NAME), incorporated into a new bioadhesive thermoresponsive system (BTS). Male Wistar rats were subjected to an upper and lower first molar class I cavity preparation followed by indirect pulp capping with sildenafil or L-NAME. Calcium hydroxide (CaOH2) was used as a control. The teeth and surrounding bone were properly dissected and processed for Nissl's staining. Pulp state was evaluated considering the morphological aspects of the inflammatory response, type of inflammatory infiltrate, organization of the odontoblast layer, blood vessel condition, and presence of abscesses or necrosis. The results were expressed as average of observations. The most intense inflammatory response was observed 3 days after the cavity preparation. No identified changes were detected in the dental pulp response of the molars treated with L-NAME compared with those treated with CaOH2. A dual effect was observed in the teeth treated with sildenafil. While low sildenafil concentration (0.015% w w-1) promoted effects comparable to CaOH2, at a higher concentration (0.15% w w-1), sildenafil caused a severe inflammatory response and pulp necrosis. This pioneering suggest that NO pathway activity may be a determinant in the process of dental pulp healing.